1998
DOI: 10.1095/biolreprod59.5.1077
|View full text |Cite
|
Sign up to set email alerts
|

The Selective Prostaglandin Endoperoxide Synthase-2 Inhibitor, NS-398, Reduces Prostaglandin Production and Ovulation In Vivo and In Vitro in the Rat1

Abstract: Two isoforms of prostaglandin G/H synthase, PGS-1 and PGS-2, catalyze the formation of prostaglandins (PG). Nonselective PGS inhibitors, e.g., indomethacin, reduce the number of ovulations and PG levels in many animal models. This study evaluated the effects of the selective PGS-2 inhibitor NS-398, compared to indomethacin, on ovulation number and on PG and steroid production both in vivo and in vitro in the rat. NS-398 reduced the synthesis of PGE2 in isolated, LH-stimulated preovulatory follicles incubated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(43 citation statements)
references
References 50 publications
4
39
0
Order By: Relevance
“…COX-2 catalyzes the production of prostaglandins known to be necessary for ovulation (38); mice null for COX-2 have severely impaired ovulation (39,40). COX-2 mRNA was undetectable by RT-PCR analysis in ovaries of PMSG-treated PRϩ͞Ϫ and PRKO mice but was induced rapidly by hCG in ovaries of both genotypes (Fig.…”
Section: Ovarian Expression Of Prmentioning
confidence: 95%
“…COX-2 catalyzes the production of prostaglandins known to be necessary for ovulation (38); mice null for COX-2 have severely impaired ovulation (39,40). COX-2 mRNA was undetectable by RT-PCR analysis in ovaries of PMSG-treated PRϩ͞Ϫ and PRKO mice but was induced rapidly by hCG in ovaries of both genotypes (Fig.…”
Section: Ovarian Expression Of Prmentioning
confidence: 95%
“…Accumulating evidence in multiple species including mouse (Lim et al 1997, Davis et al 1999, rat (Mikuni et al 1998, Gaytan et al 2002, sheep (Murdoch et al 1986), pig (Downey & Ainsworth 1980), monkey (Duffy & Stouffer 2002), and cattle (Peters et al 2004) indicates that intrafollicular synthesis of prostanoids in response to the LH surge is critical for the ovulatory process. The cyclooxygenase (COX)-2 enzyme, which catalyzes the rate limiting step in intrafollicular prostanoid synthesis, is induced within the granulosa layer of rat (Sirois et al 1992), equine (Sirois & Dore 1997), and bovine preovulatory follicles (Sirois 1994, Tsai et al 1996 in response to the LH surge.…”
Section: Introductionmentioning
confidence: 99%
“…The inducible type PTGS2 and PGE 2 -EP 2 receptor signaling play crucial roles in proper follicle rupture and cumulus expansion in a murine model of induced ovulation (Hizaki et al 1999, Matsumoto et al 2001, Ochsner et al 2003, Sirois et al 2004b. Pharmacological or genetical inhibition of PTGS2 activity results in potential suppression of ovulation (Espey et al 1986, Lim et al 1997, Mikuni et al 1998a. On the other hand, the involvement of the alternative LOX pathway in ovulation process was first suggested by Reich et al (1983) who demonstrated that chemical inhibition of LOX blunted ovulatory response in gonadotropins-primed immature rats.…”
Section: Introductionmentioning
confidence: 99%